Fire and Fire Mitigation by Low-Fuel Building Products - Kunigal Shivakumar; Bharath Kenchappa; Dhruva Shivakumar (Fire)
Fire is a combustion reaction where fuel reacts with oxygen in the presence of heat, releasing energy as light, heat, and flames. The main components of fire are fuel, oxygen, and heat. All three components must be present to cause a fire. Fire is a significant threat to residential and commercial buildings, often intensified by high fuel content in building materials such as wood and synthetics. This paper summarizes fire types and damages, loss of property and life, fuel content in building materials, and a method to reduce fire risk by minimizing the building material’s fuel content. This method uses minerals (coal combustion residual (CCR)), primarily inorganic oxides bonded with a small percentage of polyurethane binder, to manufacture a composite material moldable into multiple building products. The composite was tested as per the ASTM for mechanical, thermal, and fire safety performance. ASTM D635-based fire testing showed self-extinguishing behavior with significantly reduced burn rate and lengths (1–2 mm). A low calorific value of 6.6 MJ/kg was determined separately. The test results demonstrate that CCR-based mineral composites offer a fire-resistant, structurally sound, and eco-friendly alternative to wood products. This research supports recycling inorganic minerals into fire-resistant building products that enhance safety.